Wir Müssen Bleiben. Artworks and Visual Expressions Against Gentrification. The Case of Rigaer Straße Walls in Berlin - Conti, Uliano (Italian Sociological Review, 2023)
The article proposes an analysis of the visual artworks present in the Rigaer Straße area in Berlin. The artworks located in this city area are expressions of dissent against gentrification, real estate groups and other social actors, such as police. With reference to the scientific literature on urban art, the paper proposes visual artworks in Rigaer Straße as a useful element in interpreting actions of social groups in the German capital. In addition, the article proposes visual sociology as a field for analysing urban change and interpreting the city’s visual emergencies, consistently with the sociological tradition of Walter Benjamin and Siegfried Kracauer.